Progress of Spatial Acoustics in the Northern Italian Theatres and Stage Architecture during the Baroque Era - Sanvito, Paolo (Actual Problems of Theory and History of Art, 2021)
Until a few years ago, the architectural history of the Renaissance only sporadically addressed the problem of sound regulation and optimisation inside closed spaces (in German technically: Raumakustik). Instead, nowadays we are currently experiencing a flood of publications about some of the greatest European stage architects, such as Scamozzi, or the Bibiena architectural dynasty: in both cases very famous architects, to whom several symposia and exhibitions have quite recently been dedicated. Nevertheless, there have unfortunately been only isolated references to their views on the subject of theatre acoustics and very scarce research on their bequests in the field.That is why, for about a decade now and especially in Germany, where some of Europe’s leading acoustics researchers are based and where the most lively debates on concert halls have been taking place, some core questions had to decisively get addressed. First, what level of acoustics the buildings of the ancien régime have generally been reaching; and Second, what were the ways to achieve good acoustics in architecture from the early modern period to the classical period (e. g. with Haydn) and through the Romantic era. The author has been working for several years, together with numerous colleagues, primarily of the Technical University Berlin, on questions concerning the understanding of sophisticated acoustics in performance spaces.The “Audiokommunikation” team in Berlin has most recently performed the evaluation and processing of the measurement results of the the Teatro “Scientifico” in Mantua and the Teatro degli Antichi in Sabbioneta. The archived measurement results are to be analyzed using related historical data. In the process, recordings of historically documented performances can be made for both houses in the anechoic chamber of the Audio Communication Department.
Keywords: spatial acoustics; Bibiena; Palladio; stage architecture; Baroque theatre